ANALISA INDIKATOR KINERJA TEROWONGAN ANGIN RANGKAIAN TERBUKA (OPEN CIRCUIT WIND TUNNEL) TIPE SUBSONIC - Aditya, Vikra; Alchalil, Alchalil; Asnawi, Asnawi; Rahman, Abdul (E-Journal Universitas Malikussaleh, 2023)
Fluid is a substance that can change its shape continuously due to the acting tangential shear force. Aerodynamics is a branch of fluid dynamics that studies specifically the forces acting on an object contained in a fluid flow. Wind Tunnel is a tool used in aerodynamics research to study airflow characteristics. Wind tunnel performance indicators include flow uniformity, flow and pressure distribution, aerodynamic forces acting on test objects in the wind tunnel. By using unsymmetrical airfoils, the impact of speed variations of 2 m/s, 4 m/s, 6 m/s, 8 m/s, 10 m/s and increasing angles of attack ranging from 0°, 5°, 10° on fluid flow can be determined. Tests were conducted in a section of the wind tunnel measuring 30 cm x 30 cm x 40 cm. Overall, the open-type wind tunnel has not been able to create uniform flow. The Reynolds number is at Re>4,000, so the wind tunnel under study is turbulent. The results of the speed variation and angle of attack increase also have an impact on the lift and drag coefficient values of the airfoil. At the maximum speed variation of 10 m/s with an angle of attack of 10°, the lift coefficient is 0.14350 and the drag coefficient is 0.15162.